PENGARUH MODEL KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA PENDIDIK PAUD DI KECAMATAN TAKTAKAN - Iin Hasinah; Budi Ilham Maliki; Mutoharoh Mutoharoh; Yolanda Pahrul; Popy Dayurni; Galuh Mulyawan (STKIP Pesisir Selatan, 2026)
This study aims to determine the effect of transformational leadership on the performance of early childhood education (PAUD) educators in Taktakan District. Transformational leadership is considered capable of boosting educator motivation, commitment, and performance through inspirational and empowering influences. This study used a quantitative method with a causal comparative approach and a survey method. The sample size was 31 respondents, drawn from a total population of 151 early childhood education (PAUD) educators in Taktakan District. Data were collected through questionnaires and analyzed using simple linear regression analysis. The results showed that transformational leadership has a positive and significant influence on educator performance, with a coefficient of determination (R²) of 0.832 and a significance level of 0.001 (p < 0.05). This indicates that 83% of the variation in educator performance can be explained by transformational leadership, thus transformational leadership has a positive and significant influence on educator performance. Thus, transformational leadership is a crucial factor that needs to be continuously developed to improve the quality of early childhood education.